A Study of Teenagers Buying Behavior in Shopping Malls in Delhi (International Journal of Innovative Research in Engineering & Management, 2021)
Shopping malls are great place for fun and they are increasing in  number day by day. People are growing and exploring new  things in the market, and shopping malls are best place for them  to check new things and material. Teenagers are playing huge  role in the industry in this research we studied about the  behavior of the teenagers while they are buying stuffs from the  shopping mall. We are applying different methods for this study  like reading facial expression when they are buying something,  the way they talk with shopkeepers .as we are studying the  behavior of the teenagers Personality, beliefs, expectations,  emotions, and mental health are all factors to consider for this  study. Another primary determinant of a consumer's purchasing  behavior and impression of brands at shopping centers is their purchasing power. Shopping centers are a great place for a  family excursion, fun and entertainment, shopping, and dining.  In daily visitor numbers at shopping centers, the age of the  customer is the most crucial element. Consumers today go to  different shopping malls, which has an influence on their  purchasing habits. We have taken 100 peoples randomly from  different malls in Delhi and studied their behavior. As a result  we found out that the behavior is totally dependable from person  to person it is varying from teen to teen. The future scope of this  study is consumer behavior analyzes the what, when, where,  why, and how consumers make choices, focusing on the what,  when, where, why, and how of product consumption.  Companies, for example, seek to know why people purchase  things and what sorts of demands are met via consumption.
Keywords: Advertising; Customer; Purchasing Behavior; Retail Sector; Shopping Malls